THEORETICAL BASES OF THE TERRITORIES' STEADY ECONOMIC GROWTH - O. Zakirova (Russian Journal of Economics and Law)
The article views the economic category of budget. The mechanism of regional budgets of the Russian Federation subjects' formation is analyzed.